Temporomandibular Disorders in Females: Acupuncture Compared to Occlusal Splint - Alves Rezende, Maria Cristina Rosifini; Sant’Anna, Crischina Branco Marques; Aguiar, Sandra Maria Herondina Coelho Avila de; Bertoz, André Pinheiro de Magalães; Hall, Kevin Bruce; Dyonisio, Ana Luiza Di Bella; Lima, Jacquelyne do Valle; Costa, Leonardo Portilha Gomes da; de Oliveira, João Augusto Guedes; Alves Rezende, Luis Guilherme Rosifini (ARCHIVES OF HEALTH INVESTIGATION, 2013)
Objective: To compare the effect of acupuncture and occlusal splint in the treatment of temporomandibular disorders (TMD) in female patients.Method: Forty-eight female patients (mean age of 39.3±6.8 years) with diagnosed pain in muscles or joint according to RDC/TMD criteria were attended at UNESP - Aracatuba Dental School. Including criteria were reported pain in the chewing muscles and/or in the temporomandibular joint measured by a visual analogue scale (range from 0 to 10) and a reported reduction of the maximum mouth opening. Excluding factors were major occlusal problems, systemic diseases, pregnancy and age below 18 years. After randomization, the first group was treated with acupuncture performed by instructed dentist. The second group was treated with occlusal splint. The outcome variables were assessed at baseline (prior to the first treatment session) and after 1, 3 and 6 months. Primary criteria of success were improvement of mouth opening and pain reduction.Result: Acupuncture group exhibited chewing pain decrease from 5 (at baseline) to 1, 2 and 1 after 1, 3 and 6 months, respectively. In the splint group, chewing pain decreased from 4 to 2, 1 and 2 after 1, 3 and 6 months, respectively. The mouth opening (in mm) increased from 28 (at baseline) to 42, 44 and 46 after 1, 3 and 6 months, respectively in the acupuncture group. In the splint group, mouth opening improved from 29 to 40 after 1 month, and to 43 and 42 after 3 and 6 months. A significant pain reduction was noted for both groups when compared to the baseline (p<.001; Wilcoxon test). Acupuncture group had a significant clinical improvement of opening mouth (Mann-Whitney). Conclusion: The present outcomes suggest a positive association among acupuncture and occlusal splint on the reduction of chewing pain. Acupuncture was more effective in the mouth opening increase. Keywords: Dental Occlusion; Pain; Masticatory Muscles; Therapeutics.